Molecular epidemiology and strain diversity of circulating feline Calicivirus in Thai cats - Phongroop, Kannika; Rattanasrisomporn, Jatuporn; Piewbang, Chutchai; Tangtrongsup, Sahatchai; Rungsipipat, Anudep; Techangamsuwan, Somporn (Frontiers in Veterinary Science, 2024)
Feline calicivirus (FCV) is a significant viral pathogen causing upper respiratory tract and oral diseases in cats. The emergence of the virulent systemic FCV variant (VS-FCV) has raised global concern in the past decade. This study aims to explore the epidemiology, genetic characterization, and diversity of FCV strains circulating among Thai cats. Various sample types, including nasal, oral, and oropharyngeal swabs and fresh tissues, were collected from 184 cats across different regions of Thailand from 2016 to 2021. Using reverse transcription real-time polymerase chain reaction (RT-qPCR), FCV infection was investigated, with additional screening for feline herpesvirus-1 (FHV-1) by qPCR. The detection rates for FCV, FHV-1, and co-infection were 46.7%, 65.8%, and 31.5%, respectively. Significantly, the odds ratio (OR) revealed a strong association between the detection of a single FCV and the presence of gingivostomatitis lesions (OR: 7.15, 95% CI: 1.89 -26.99, p = 0.004). In addition, FCV detection is notably less likely in vaccinated cats (OR: 0.22, 95% CI: 0.07-0.75, p = 0.015). Amino acid sequence analysis based on the VP1 major capsid protein gene of the 14 FCV-Thai (FCV-TH) strains revealed genetic diversity compared to the other 43 global strains (0% to 86.6%). Intriguingly, a vaccine-like FCV variant was detected in one cat. In summary, this study provides insights into the epidemiology and molecular characteristics of FCV diversity within the Thai cat population for the first time. The identification of unique physicochemical characteristics in the capsid hypervariable region of some FCV-TH strains challenges previous hypotheses. Therefore, further exploration of vaccine-like FCV variants is crucial for a comprehensive understanding and to improve viral prevention and control strategies.